Performance comparison of image normalisation method for DNA microarray data - Baans, Omar Salem Nasser; Bahari Jambek, Asral; Hashim, Uda; Yusof, Nor Azah (Universiti Putra Malaysia Press, 2017)
Normalisation is a process of removing systematic variation that affects measured gene expression levels in microarray experiment. The purpose is to get a more accurate DNA microarray result by deleting the systematic errors that may have occurred when making the DNA microarray slid. In this paper, four normalisation methods of Global, Lowess, Quantile and Print-tip are discussed, tested and their final results compared in the form of Matrixes and graphs. Ideal and real microarray slides have been used for this project. It was found that the Print-tip normalisation method showed the closest results to the real result for an ideal microarray slide and it has a straight median line final graph. The Print-tip normalisation method uses more than one normalization factor that is divided among intervals which are dependent on the values of the addition of red and green logarithm.